SUPPORTING FOOD SECURITY AND ORGANIC VEGETABLE PLANTING FOR THE COMMUNITY DURING PANDEMIC IN WARUNGPRING DISTRICT, PEMALANG - Muhammad Haikaludin; Fatiatun Fatiatun (Jurnal Layanan Masyarakat (Journal of Public Services), 2022)
One of the problems that occurred during the COVID-19 pandemic was the weakening of community food security as a result of policies to reduce work activities outside the home which aims to prevent the spread of the virus as a result of the reduced activity so far having to be outside the home. For this reason, efforts are needed to meet the daily needs of the community that can be done without activities outside the home. The problem that exists is the lack of public knowledge about how to fulfill food needs. The utilization of land around the house can be used as a solution to this problem, namely by growing organic vegetables that can be used to meet daily food needs.